2018
DOI: 10.1186/s12938-018-0593-2
|View full text |Cite
|
Sign up to set email alerts
|

Regressing grasping using force myography: an exploratory study

Abstract: BackgroundPartial hand amputation forms more than 90% of all upper limb amputations. This amputation has a notable effect on the amputee’s life. To improve the quality of life for partial hand amputees different prosthesis options, including externally-powered prosthesis, have been investigated. The focus of this work is to explore force myography (FMG) as a technique for regressing grasping movement accompanied by wrist position variations. This study can lay the groundwork for a future investigation of FMG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These 48 gestures included 16 grasp types, 16 sign language gestures, and 16 finger and hand movements. For continuous actions, Sadeghi et al showed that the angle between index-and-thumb and the one between the middle finger-and-thumb could be accurately predicted using signals extracted near the wrist [33]. In this study, the authors also accounted for different wrist positions while predicting the angles.…”
Section: Fmg Signal Acquisitionmentioning
confidence: 92%
See 1 more Smart Citation
“…These 48 gestures included 16 grasp types, 16 sign language gestures, and 16 finger and hand movements. For continuous actions, Sadeghi et al showed that the angle between index-and-thumb and the one between the middle finger-and-thumb could be accurately predicted using signals extracted near the wrist [33]. In this study, the authors also accounted for different wrist positions while predicting the angles.…”
Section: Fmg Signal Acquisitionmentioning
confidence: 92%
“…The percentages shown in the figure include some of the work that used multiple classifications algorithms for performance comparison; the percentage is based on the total instance that each method was used and not on the number of publications. As shown in the figure, 37% of the publications use linear discriminant analysis (LDA), 23% use support vector machine (SVM), 15% use artificial neural network (ANN), and the rest use k-nearest neighbor (KNN) [9,31,37], decision tree (DT) [9], deep neural network (DNN) [59,60], extreme learning machine (ELM) [28,55], Gaussian process regression (GPR) [65], hidden Markov model (HMM) [9], random forest (RF) [33,66], and tree bagging (TB) [67].…”
Section: Fmg Processing Methodsmentioning
confidence: 99%
“…where y k is the expected value of the reading, y k is the predicted value, y k is the mean of expected values, n is the number of observations, and range y is the range of values in observations of expected values. R 2 and RMSE% are commonly used for assessment of performance of regression methods [50]. Based on these outcome measures, one of the regression algorithms was chosen to be used in this study.…”
Section: Regression Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated FMG to be a promising HMI for upper limb prosthesis control (Cho et al, 2016;Radmand et al, 2016;Ahmadizadeh et al, 2017;Jiang et al, 2017;Sadeghi Chegani and Menon, 2018). FMG monitors changes in volumetric pattern of user's forearm and detects intentions of the user based on these changes (Rasouli et al, 2016).…”
Section: Application Backgroundmentioning
confidence: 99%